Improving Youth Unemployment Issues and Further Development of Youth Policies in the European Union member states - Pkhakadze, Tamar (Technium Social Sciences Journal, 2022)
Young people are the most important part of the country’s labour resources and a strategic resource for socio-economic development. Employment of young people requires special assistance and support. They are distinguished from other socio-demographic groups of the population by their health, level of education, vocational training, mobility, high demands on work, etc. It is necessary to establish mechanisms and set goals through ministries, local governments, youth organizations, the private sector, civil society and international organizations to improve the various problems or challenges facing young people. Solving the employment problems of young people requires a special approach because it is the youth who are the most active part of society, which reacts strongly to social injustice. This chapter will summarize all the issues mentioned in the previous chapter and offer possible solutions for improving the youth unemployment problem.